1999
DOI: 10.1002/(sici)1521-379x(199905)51:5<157::aid-star157>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Starch Granules Trapped and Heated Using Optical Tweezers

Abstract: The heat capacity values of 1 % aqueous dispersions of barley and maize starches with different amylose content (1-35 %), were determined. It was shown that a rise in amylose content leads to an increase of heat capacity values. The heat capacity values were calculated per

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Investigations of the swelling process of individual starch granules heated in excess water have revealed that the swelling magnification of Tanikei A6599‐4 starch granules is less than that of amylose‐free waxy wheat starch but similar to that of non‐waxy wheat starch. [ 11 ] In gel‐dispersed dynamic viscoelasticity measurements, the dynamic modulus ( G ′) and dynamic loss ( G ″) properties of Tanikei A6599‐4 starch are higher than those of amylose‐free waxy wheat starch. [ 12 ] These findings indicate that the swollen starch granules of Tanikei A6599‐4 are more rigid than the swollen starch granules of amylose‐free waxy wheat, and this increased rigidity of starch granules might underlie the stable hot‐paste viscosity; however, little information is available to explain why the starch granules of Tanikei A6599‐4 are rigid.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the swelling process of individual starch granules heated in excess water have revealed that the swelling magnification of Tanikei A6599‐4 starch granules is less than that of amylose‐free waxy wheat starch but similar to that of non‐waxy wheat starch. [ 11 ] In gel‐dispersed dynamic viscoelasticity measurements, the dynamic modulus ( G ′) and dynamic loss ( G ″) properties of Tanikei A6599‐4 starch are higher than those of amylose‐free waxy wheat starch. [ 12 ] These findings indicate that the swollen starch granules of Tanikei A6599‐4 are more rigid than the swollen starch granules of amylose‐free waxy wheat, and this increased rigidity of starch granules might underlie the stable hot‐paste viscosity; however, little information is available to explain why the starch granules of Tanikei A6599‐4 are rigid.…”
Section: Introductionmentioning
confidence: 99%